Gazal al-Auṭān wa al-Buldān fῑ Syi’r Māni’ Sa’ῑd al-‘Utaibah - Saleh Ahmad Alhameed; Noor Hasma Mohammed Saad; Bader Ulmonir Mohammad Noor (IAIN Salatiga, 2023)
The study examines courtly love themes in the homeland and country of the Emirati poet Manaa Saeed al-Otaiba through his two Diwan,